Kinesin-13 Regulates Flagellar, Interphase, and Mitotic Microtubule Dynamics in Giardia intestinalis - Dawson, Scott C. (American Society for Microbiology (ASM), 2007)
Microtubule depolymerization dynamics in the spindle are regulated by kinesin-13, a nonprocessive kinesin motor protein that depolymerizes microtubules at the plus and minus ends. Here we show that a single kinesin-13 homolog regulates flagellar length dynamics, as well as other interphase and mitotic dynamics in Giardia intestinalis, a widespread parasitic diplomonad protist. Both green fluorescent protein-tagged kinesin-13 and EB1 (a plus-end tracking protein) localize to the plus ends of mitotic and interphase microtubules, including a novel localization to the eight flagellar tips, cytoplasmic anterior axonemes, and the median body. The ectopic expression of a kinesin-13 (S280N) rigor mutant construct caused significant elongation of the eight flagella with significant decreases in the median body volume and resulted in mitotic defects. Notably, drugs that disrupt normal interphase and mitotic microtubule dynamics also affected flagellar length in Giardia. Our study extends recent work on interphase and mitotic kinesin-13 functioning in metazoans to include a role in regulating flagellar length dynamics. We suggest that kinesin-13 universally regulates both mitotic and interphase microtubule dynamics in diverse microbial eukaryotes and propose that axonemal microtubules are subject to the same regulation of microtubule dynamics as other dynamic microtubule arrays. Finally, the present study represents the first use of a dominant-negative strategy to disrupt normal protein function in Giardia and provides important insights into giardial microtubule dynamics with relevance to the development of antigiardial compounds that target critical functions of kinesins in the giardial life cycle.